Design and initial results of a turn-by-turn beam position monitoring system for multiple bunch operation of the ATF damping ring - Christian, G; Apsimon, R; Bett, DR; Burrows, P; Davis, MR; Gerbershagen, A; Perry, C; Constance, B; Resta-Lopez, J (2011)
An FPGA-based monitoring system has been developed to study multi-bunch beam instabilities in the damping ring (DR) of the KEK Accelerator Test Facility (ATF), utilising a stripline beam position monitor (BPM) and existing BPM processor hardware. The system is designed to record the horizontal and/or vertical positions of up to three bunches in the DR in single-bunch multi-train mode or the head bunch of up to three trains in multi-bunch mode, with a bunch spacing of 5.6 ns. The FPGA firmware and data acquisition software were modified to record turn-by-turn data for up to six channels and 1-3 bunches in the DR. An overview of the system and initial results will be presented. Copyright © 2011 by IPAC'11/EPS-AG.